2021
DOI: 10.3390/ijms22094764
|View full text |Cite
|
Sign up to set email alerts
|

Replication Stress, Genomic Instability, and Replication Timing: A Complex Relationship

Abstract: The replication-timing program constitutes a key element of the organization and coordination of numerous nuclear processes in eukaryotes. This program is established at a crucial moment in the cell cycle and occurs simultaneously with the organization of the genome, thus indicating the vital significance of this process. With recent technological achievements of high-throughput approaches, a very strong link has been confirmed between replication timing, transcriptional activity, the epigenetic and mutational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 187 publications
(292 reference statements)
0
13
2
Order By: Relevance
“…Strikingly, we found that the number of gene-level gains and heterozygous losses dwarfed that observed for amplifications, homozygous deletions, or mutations. Additionally, copy number trends associated with replication timing did not correlate with our findings (28); MYBL2 High tumors acquired similar numbers of gains and heterozygous losses across both ERFS and MiDAS loci, with a trend toward more heterozygous losses ( Figure 4C ). This data is consistent with previous findings where elevated MMEJ activity is coincident with increased loss of heterozygosity events (29).…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…Strikingly, we found that the number of gene-level gains and heterozygous losses dwarfed that observed for amplifications, homozygous deletions, or mutations. Additionally, copy number trends associated with replication timing did not correlate with our findings (28); MYBL2 High tumors acquired similar numbers of gains and heterozygous losses across both ERFS and MiDAS loci, with a trend toward more heterozygous losses ( Figure 4C ). This data is consistent with previous findings where elevated MMEJ activity is coincident with increased loss of heterozygosity events (29).…”
Section: Resultscontrasting
confidence: 72%
“…These circumstances make MiDAS genes difficult to replicate and cells frequently commit to mitosis prior to completing replication at these sites. Late replicating genomic regions have been associated with increased deletions as cells use various methods to complete replication (28). Given this, we hypothesized that MYBL2 High tumors acquire greater numbers of genomic alterations at replication stress sensitive (RSS) sites.…”
Section: Resultsmentioning
confidence: 99%
“…The availability of initiation factors naturally limits the number of origins that may be fired early and selects the remaining origins to be fired late [ 63 ]. Alterations in replication timing are mutually dependent on the structure of the genome, including its sequence and epigenetic pattern (reviewed in [ 64 ]). RIF1 prevents middle/late origin firing by mechanisms that are presented in subsequent sections [ 13 ].…”
Section: Replication Timingmentioning
confidence: 99%
“…Genomic instability supports the fast accumulation of genetic and epigenetic changes fueling cancer transformation, and otherwise impairs normal cellular functioning [ 78 ]. Replication stress, a phenomenon causing stalling, breakage, or collapse of replication fork, affects RT (reviewed in [ 64 , 79 ]). Replication stress is targeted by DDR, the main collective mechanism to maintain genomic stability [ 80 ].…”
Section: Rif1 In Replication Timingmentioning
confidence: 99%
“…RT is triggered at certain point during cell cycle and its development is synchronized with changes in genome organization. RT is connected to processes like 3D genome organization, transcription, epigenetic modulation and mutation, and spatial distribution, and is thought to influence replicative stress and consequently genomic stability (Briu et al 2021).…”
mentioning
confidence: 99%